Constructing Social Harmony through Mercy-Based Education: Insights from the Prophetic Model - Arifuddin Arifuddin; Abdul Rahim Karim; M. Ilham; Muhammad Irfan Hasanuddin (Universitas Islam Negeri Walisongo Semarang, Indonesia, 2025)
Prophet Muhammad SAW is known as a plenary figure who succeeded in transforming the pluralistic society of Medina into a harmonious and just community. This success is inseparable from his educational strategy that utilizes spiritual, social, and intellectual capital. This research uses a qualitative approach with a literature study method. Data sources were obtained from books of the Prophetic Sirah, hadith, and contemporary academic literature. The analysis was done thematically to identify the principles and educational strategies used by the Prophet in the social context of Medina. The research found that the Prophet Muhammad's educational strategy was rooted in the values of compassion, wisdom, and dialog. These strategies established a peaceful and inclusive social order. These values remain relevant to be applied in addressing contemporary social challenges, such as intolerance, identity crisis, and social fragmentation. This finding confirms the importance of actualizing mercy-based education in building a civilized society.